2019
DOI: 10.1038/s41598-019-53533-3
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Campylobacter infection and association with growth and enteric inflammation in children under 2 years of age in low-resource settings

Abstract: Campylobacter species infections have been associated with malnutrition and intestinal inflammation among children in low-resource settings. However, it remains unclear whether that association is specific to Campylobacter jejuni/coli. The aim of this study was to assess the association between both all Campylobacter species infections and Campylobacter jejuni/coli infections on growth and enteric inflammation in children aged 1–24 months. We analyzed data from 1715 children followed from birth until 24 months… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

4
6

Authors

Journals

citations
Cited by 33 publications
(51 citation statements)
references
References 30 publications
3
47
1
Order By: Relevance
“…1 ). Several pathogens identified among the rhesus macaques are associated with human growth stunting and include Campylobacter 8 10 , 28 – 30 , Shigella 29 , 31 , enterotoxigenic Escherichia coli (ETEC) 28 , 29 , Cryptosporidium 29 , 31 , Entamoeba histolytica 32 , 33 , and Giardia 29 , 34 . Although diarrheal disease is relatively common among outdoor-housed non-human primates (NHP) 16 18 , 27 , none of the 1-month-old infants ( n = 80) presented with clinical diarrhea at the time of screening for enteric pathogens.…”
Section: Resultsmentioning
confidence: 99%
“…1 ). Several pathogens identified among the rhesus macaques are associated with human growth stunting and include Campylobacter 8 10 , 28 – 30 , Shigella 29 , 31 , enterotoxigenic Escherichia coli (ETEC) 28 , 29 , Cryptosporidium 29 , 31 , Entamoeba histolytica 32 , 33 , and Giardia 29 , 34 . Although diarrheal disease is relatively common among outdoor-housed non-human primates (NHP) 16 18 , 27 , none of the 1-month-old infants ( n = 80) presented with clinical diarrhea at the time of screening for enteric pathogens.…”
Section: Resultsmentioning
confidence: 99%
“…Low maternal MUAC was defined as a MUAC < 23 cm, which correlates closely with low BMI (Ghosh et al, 2019;Sultana et al, 2015). Length-for-age (LAZ), weight-for-age (WAZ) and weight-for-length (WLZ) Z scores were calculated as indicators of child nutritional status according to the 2006 WHO Standards For Children, using Z-score scale = (observed value À average value of the reference population)/standard deviation value of reference population (Haque et al, 2019;Onis & Bloessner, 1997).…”
Section: Variables Of Interestmentioning
confidence: 99%
“…We found higher maternal education was protective for aaiC and Aar genomic strain of EAEC. Findings from several other studies conducted in the MAL-ED settings also found an association of these factors with EAEC and Campylobacter infection 31 , 32 .…”
Section: Discussionmentioning
confidence: 57%